PIPN Life Skill: Creating motorcycle workshop entrepreneurs for unemployed communities in Nagari Sialang Gaung - Milana, Milana; Hidayat, Nuzul; Putra, Dwi Sudarno; Baharudin, Agus; Purwanto, Wawan (Universitas Muhammadiyah Magelang, 2025)
The high unemployment rate in Nagari Sialang Gaung, reaching 30–40% of the productive-age population, poses a serious problem hindering community welfare. This situation is paradoxical given the significant opportunities in the motor vehicle service sector, driven by an estimated 10% annual increase in the number of motorcycles. Unfortunately, this market potential remains largely untapped due to the lack of technical and entrepreneurial skills among the unemployed youth. The Prodi and Nagari Integration Program (PIPN) Life Skill was established to bridge this gap with a dual objective, enhancing motorcycle mechanic competence and fostering entrepreneurship through hands-on practice. The program was comprehensively designed, encompassing needs analysis, development of a curriculum based on local potential, technical training (covering both conventional and EFI injection systems), instruction in workshop management, and post-training business mentoring. Program results indicate a significant increase in participant competence, with 85% demonstrating the ability to perform repairs independently and 30% having successfully initiated small-scale repair businesses. This success underscores the critical importance of synergy between universities and village governance in empowering communities based on sustainable local potential, thereby contributing directly to the achievement of the Sustainable Development Goals (SDGs).